ASSOCIATION OF THE MONONUCLEOTIDE POLYMORPHISMS RS62116755 OF GENE GACAT3, RS12170546 OF GENE PARVB, RS16994849 OF GENE PLCB1, RS78143315 OF GENE PDCD6IP WITH SUDDEN CARDIAC DEATH - А. А. Ivanova; V. N. Maksimov; S. К. Malyutina; V. P. Novoselov; S. V. Savchenko; М. I. Voevoda (Российский кардиологический журнал)
Aim. To check the association of sudden cardiac death (SCD) with mononucleotide polymorphisms rs62116755 gene GACAT3, rs12170546 gene PARVB, rs16994849 gene PLCB1, rs78143315 gene PDCD6IP, that were set as genetic markers of SCD in previous full-genome associative original study.Material and methods. Group of SCD (n=388, mean age 52,9±9,2 y.o., males — 77,2%, females — 22,8%) was formed by the SCD criteria of World Health Organization and European Society of Cardiology. Controls matched by sex and age (n=387, mean age 52,4±8,8 y.o., males — 62,3%, females — 37,7%) from the DNA banks of international studies MONICA, HAPIEE. Separation of DNA was done with the phenol-chlorophorm extraction. Genotyping was done by polymerase chain reaction with further polymorphism analysis of the lengths of restrictional fragments.Results. There was no association with SCD of the mononucleotide polymorphisms rs62116755 gene GACAT3, rs78143315 gene PDCD6IP. In SCD group the number of TT carriers rs12170546 gene PARVB was significantly lower than in controls (OR =1,66, 95% CI 1,25-2,21, p=0,001; OR =0,67, 95% CI 0,50-0,90, p=0,009, respectively). In the group younger than 50 y.o. the number of GG carriers rs16994849 gene PLCB1 was significantly higher, and of genotype AA — lower, comparing to the controls (OR =4,92, 95% CI 1,01-23,20, p=0,032; OR =0,54, 95% CI 0,31-0,93, p=0,029, respectively). In males older than 50 the part of GG carriers rs16994849 gene PLCB1 was significantly lower than in control group (OR =0,11, 95% CI 0,01-0,91, p=0,024).Conclusion. Mononucleotide polymorphisms rs62116755 gene GACAT3, rs78143315 gene PDCD6IP were not related to SCD. Genotype ТТ of polymorphism rs12170546 gene PARVB is a genotype of risk of SCD, and genotype TC is protective. Genotype GG of polymorphism rs16994849 gene PLCB1 is the genotype of risk for SCD for those younger than 50 y.o. and is protective in those older than 50. Genotype AA of polymorphism rs16994849 gene PLCB1 is protective against SCD in those younger 50 y.o.